2020
DOI: 10.21203/rs.3.rs-110214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors Associated With Frequency of Antenatal Visits, Number of Items of Antenatal Care Contents Received and Timing of First Antenatal Care Visits in Ethiopia: Multilevel Mixed-Effects Analysis

Abstract: Background: An improved quality Antenatal care (ANC) from skilled providers is essential to pregnant women so that ensure the key health circumstances for mother and child during pregnancy. Thus, this study attempted to assess which risk factors are significantly associated with the timing of antenatal care, the number of antenatal care visits, and the number of items of antenatal care contents received from skilled providers in the recent pregnancy among mothers in Ethiopia. Methods: Data was extracted from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Even though the rate is still low, this improvement could be explained by the rigorous interventions the government of Uganda has put in place for the past decade to improve maternal health outcomes. Moreover, the nding was higher compared to a study conducted in Kenya 10.9% [17] and almost similar with one conducted in Ethiopia (20.1%) which explored DHS data of 2016 [19].…”
Section: Discussionsupporting
confidence: 70%
“…Even though the rate is still low, this improvement could be explained by the rigorous interventions the government of Uganda has put in place for the past decade to improve maternal health outcomes. Moreover, the nding was higher compared to a study conducted in Kenya 10.9% [17] and almost similar with one conducted in Ethiopia (20.1%) which explored DHS data of 2016 [19].…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, studies indicate that rural resident women were significantly less likely to have higher numbers of content items of ANC services. 9 , 20 , 22 , 41 Rural women have substantially less or even absent transportation infrastructure which makes access to healthcare difficult and may contribute to the difference. 52 The study also revealed long distances to health institutions and low media exposure among rural women contributed to inadequate received ANC components.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, previous studies showed that as education increases, number of received ANC content also increases. 9 , 22 , 42 , 50 , 51 , 55 Relatively affordable and accessible health information for educated women compared to those who never attended schools may explain the associations. 56 Furthermore, education fosters maternal healthcare awareness, appropriate need-based services utilization, 17 , 20 , 57 household maternal decision-making ability, 57 autonomy on their health, 58 new values and attitudes that favor modern health care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations